INTEGRITAS SEBAGAI PEMODERASI PENGARUH KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT - Ayuni, Winda Asri; Herkulanus, Bambang Suprasto (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The complexity of the audit is one of the things that is often experienced by auditors in performing audit tasks. The purpose of this study is to determine the effect of task complexity on the quality of the audit and determine the integrity as a moderating influence on the quality of the audit task complexity. This research was conducted at the KAP in Bali and East Java. The data used in this study are primary data obtained by distributing questionnaires directly to the respondent. The samples used in this study amounted to 49 obtained by using purposive sampling method. Data analysis techniques used in this study are Moderated Regression Analysis (MRA). The results of this study stated that the complexity of the task negative effect on audit quality and integrity can moderate (weaken) the effect of the complexity of the task to audit quality.
Keywords: Kompleksitas Tugas, Integritas, Kualitas Audit